Balloon catheter use for cervical ripening in women with term pre‐labor rupture of membranes: A 5‐year cohort study. (12th April 2020) - Kruit, Heidi; Tolvanen, Jenna; Eriksson, Jasmin; Place, Katariina; Nupponen, Irmeli; Rahkonen, Leena
Abstract: Introduction: To investigate the safety of balloon catheter for cervical ripening in women with term pre‐labor rupture of membranes (PROM) and to compare the incidence of maternal and neonatal infections in women with PROM and women with intact membranes undergoing cervical ripening with a balloon catheter. Material and methods: This retrospective cohort study of 1923 women with term singleton pregnancy and an unfavorable cervix undergoing cervical ripening with a balloon catheter was conducted in Helsinki University Hospital between January 2014 and December 2018. For each case of PROM, two controls were assigned. The main outcome measures were the rates of maternal and neonatal infections. Statistical analyses were performed by SPSS. Results: In all, 641 (33.3%) women following PROM and 1282 (66.6%) women with intact amniotic membranes underwent labor induction. The rates of intrapartum infection (3.7% vs 7.7%; P = .001) and neonatal infection (1.7% vs 3.8%; P = .01) were not increased in women induced by balloon catheter following PROM. Intrapartum infections were associated with nulliparity (odds ratio [OR] 3.3, 95% confidence interval [CI] 1.6‐6.5), history of previous cesarean section (OR 2.8, 95% CI 1.2‐6.4), extended gestational age ≥41 weeks (OR 1.9, 95% CI 1.2‐3.0) and an induction to delivery interval of 48 hours or more (OR 2.0, 95% CI 1.2‐3.3). The risk of neonatal infection was associated with nulliparity (OR 3.3, 95% CI 1.4‐8.0), gestational age ≥41 weeks (OR 1.9, 95% CI 1.09‐3.36) and induction to delivery interval of 48 hours or more (OR 3.4, 95% CI 1.9‐6.0). Conclusions: Use of balloon catheter in women with term PROM appears safe and was not associated with increased maternal or neonatal infectious morbidity.